Subjetividade e cultura digital: o papel das redes sociais na produção de novas imagens de feminilidade - Moreira, Maraisa Marques (2024)
This project proposes to investigate the processes of subjectivation and the production of new images of femininity in the digital environment. The focus is on hypermediatic communication dynamics in digital social networks and the semiotic-psychoanalytic dimensions in discourses and aesthetic narratives of the self. Technological expansion in all areas of life has transformed conceptions of image, subject, identity, time, and space, opening new possibilities for articulation of these instances, rekindling discussions about how each one represents themselves. Based on the assumption that our interaction is influenced by images and representations, this research investigates how the increasing importance and circulation of the image is impacting subjectively historically underrepresented groups, such as women in this specific case. It is of interest to know how they are challenging social stereotypes now that they are taking control of the narrative, sharing their stories, viewpoints, and contributing to the creation of new representations of femininity. The questions proposed to be answered are: with what tools does a woman constitute herself in contemporary society? What images and characteristics define what it means to be a woman today? To what powers are they subjected? And, ultimately, what is the impact of the digital revolution on the subjectivity of contemporary women? The project is justified for being a current and relevant theme for the field of communication, considering the connection between the dialogical nature of language and the constitution of the self. In general, the strength and weight that gender identity issues represent today highlight the need to look more closely at their implications, aiming to achieve a greater awareness of their sociocultural impacts. To this end, it is proposed to adopt an approach that starts from psychoanalytic semiotics, passing through feminist theories to the role of images in the production of meanings